Geoinformation mapping of anthropogenically transformed landscapes of Bila Tserkva (Ukraine) - Vadym Belenok; Liliia Hebryn-Baidy; Nataliia Bielousova; Halyna Zavarika; Oksana Sakal; Andriy Kovalenko (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The main purpose of the study is the analysis and assessment of anthropogenically transformed landscapes of Bila Tserkva (Ukraine) based on a combination of remote sensing methods and GIS mapping